EVALUATION OF NATURAL PLANT EXTRACTS, ANTAGONISTS AND FUNGICIDES AGAINST EARLY BLIGHT CAUSED BY A. SOLANI IN VITRO - R. S. ROOPA; K. B. YADAHALLI; M. C. KAVYASHREE (The Bioscan, 2014)
Early blight (Alternaria solani) of tomato is most destructive disease in tropical and subtropical countries. In natural epidemics, early blight is strongly influenced by environmental conditions causing the Leaf blight, stem blight and apical fruit rot. The bio assay of fungicides, botanicals and bio agents forms the prerequisite for the field evaluation. In vitro evaluation of twelve fungicides, six bioagents and ten botanicals against Alternaria solani casing early blight of tomato revealed that contact fungicidemancozeb @ 0.2%, systemic fungicide, hexaconazole @ 0.1 % and the combi fungicide Hexazconazole 4% + Zineb 68% @ 0.2%recorded the maximum inhibition of 87.21% 88.88%, 88.88% mycelial growth respectively. Among the bioagents tested Trichoderma harzianum found effective in inhibiting the mycelial growth (77.50%) followed by T. viride (75.14%). Among the ten plant extracts evaluated, Jatropa leaf extract @ 10per cent was found to be effective in inhibiting the mycelial growth of A. solani (62.78%). The efficacy of fungicides, bioagents and botanicals can be further evaluated in combinations of spray options under field conditions.